Evaluation of e-liquid toxicity using an open-source high-throughput screening assay - Sassano, M. Flori; Davis, Eric S.; Keating, James E.; Zorn, Bryan T.; Kochar, Tavleen K.; Wolfgang, Matthew C.; Glish, Gary L.; Tarran, Robert (PLOS Biology, 2018)
Author summary The e-liquids used in electronic cigarettes (E-cigs) typically consist of a mixture of propylene glycol (PG), vegetable glycerin (VG), and nicotine, as well as numerous chemical additives that are used for flavoring. There are currently over 7,700 different flavored e-liquids that are commercially available, but there is very limited information regarding either their chemical composition or toxicity. In this work, we developed a high-throughput screening (HTS) assay to rapidly triage and validate the toxicity of multiple e-liquids in parallel. Our data indicated that e-liquids are extremely heterogeneous, so we also performed gas chromatography–mass spectrometry (GC-MS) of all e-liquids to evaluate their composition/toxicity relationship. We found that the presence of either vanillin or cinnamaldehyde in e-liquids was associated with higher toxicity values. In addition, our data demonstrated that the PG/VG vehicle by itself was toxic at higher doses. We have also developed a publicly available and searchable website (www.eliquidinfo.org) that contains these chemical composition and toxicity data. Given the large numbers of available e-liquids, this website will serve as a resource to disseminate this information. Our HTS approach may serve as a roadmap to enable bodies such as the United States Food and Drug Administration (FDA) to better regulate e-liquid safety.